Lower trait frontal theta activity in mindfulness meditators - Guaraci Ken Tanaka; Caroline Peressutti; Silmar Teixeira; Mauricio Cagy; Roberto Piedade; Antonio Egídio Nardi; Pedro Ribeiro; Bruna Velasques (Arquivos de Neuro-Psiquiatria)
Acute and long-term effects of mindfulness meditation on theta-band activity are not clear. The aim of this study was to investigate frontal theta differences between long- and short-term mindfulness practitioners before, during, and after mindfulness meditation. Twenty participants were recruited, of which 10 were experienced Buddhist meditators. Despite an acute increase in the theta activity during meditation in both the groups, the meditators showed lower trait frontal theta activity. Therefore, we suggested that this finding is a neural correlate of the expert practitioners’ ability to limit the processing of unnecessary information (e.g., discursive thought) and increase the awareness of the essential content of the present experience. In conclusion, acute changes in the theta band throughout meditation did not appear to be a specific correlate of mindfulness but were rather related to the concentration properties of the meditation. Notwithstanding, lower frontal theta activity appeared to be a trait of mindfulness practices.